Kiai as Socialization Agents: Shaping Santri Identity to Foster Tolerance in the Context of Diversity - Rofiq, Ainur (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
The increasing challenges of religious intolerance in plural societies highlight the strategic role of Islamic educational institutions in shaping inclusive religious identities. Pesantren, as one of the oldest Islamic educational institutions in Indonesia, place the kiai at the center of religious, moral, and social guidance for santri. As authoritative figures, kiai function not only as religious teachers but also as socialization agents who influence how santri perceive and respond to diversity. This study aims to analyze the role of kiai as socialization agents in shaping santri identity to foster tolerance within the context of social and religious diversity. This research employs a library research method by critically reviewing scholarly articles, books, and peer-reviewed journals indexed in Scopus and other reputable databases published between 2020 and 2025. Data were collected through systematic searches using relevant keywords related to religious leadership, identity formation, tolerance education, pesantren, and Islamic moderation. The selected literature was analyzed using qualitative content analysis to identify key themes, theoretical frameworks, and empirical findings related to the role of kiai in promoting tolerance. The findings indicate that kiai play a pivotal role in constructing santri identity through processes of value internalization, role modeling, and institutionalization of moderate Islamic teachings. Through continuous interaction, exemplary behavior, and authoritative interpretation of religious texts, kiai successfully cultivate inclusive attitudes among santri toward interfaith and social diversity. The study also reveals that pesantren function as effective socialization spaces where tolerance is embedded as a lived practice rather than merely a normative concept. These findings imply that strengthening the role of kiai in promoting religious moderation is essential for sustaining social harmony in pluralistic societies.